Penerapan Media Pembelajaran Video Dokumenter Materi Hutan Mangrove pada Mahasiswa Program Studi Kimia UNCP - Asri Asri (Jurnal Studi Guru dan Pembelajaran, 2021)
The research objective to apply documentary video media in learning of increase knowledge chemistry study program students. Documentary video containing mangrove forest material to delivered using the zoom application in October 2020 as many as 14 people as a sample for direct appointment. The step research to used action method to making documentary video tools that were validated by instructional media experts to be fit for use, and evaluation questions using to google form software in online students after the learning process. The ability of students the understand material the 10 people dominant in medium category from of total sample 14 people with of percentage 72 percent. The high category learning outcomes were 3 people with of percentage 21 percent. The low category understands the material as much as 1 person with of percentage 7 percent. Learning outcomes to interpreted the ability to understand mangrove forest material uses documentary video media not good because the dominant category in medium. The Upgrade student knowledge of mangrove forest material using documentary video media gives medium category effects, and some are high categories